Introduction To Cost Accounting - Yılmaz , Halenur (Academician Publishing Book DOI Portal, 2023)
Cost Accounting is the monetary value of the resources sacrificed or forgone by businesses in order to achieve a specific goal. Since the title of this book is C̈ost Accounting,ït is important to understand the details of the concept of cost. After developing the concept of cost in our minds, it becomes easier to envision a branch of accounting based on cost. If your specific goal is to purchase this book, the monetary value of the resources you sacrificed in the purchasing process (such as the price you paid for the book) is considered as the cost. Cost Accounting is a accounting method used by businesses to calculate, track, and analyze their costs. This book will cover topics such as the fundamental concepts of cost accounting, types of costs, the cost calculation process, and how cost accounting is applied in different types of businesses.